Antibacterial and Anti-Biofilm Activities of Culture Filtrates from Schizophyllum commune, Coniothyrium sp., and Fusarium sp. - Hastuty, Aerma; Mairani, Rahma; Rosada, Keukeu Kaniawati (UI Scholars Hub, 2020)
Bacterial infections are usually caused by biofilms that are resistant to extreme conditions. Studies have shown that fungal extracts have the potential to inhibit biofilm formation. The aim of this study was to examine the activity of several fungal culture filtrates in inhibiting bacterial growth and biofilm formation. The fungi were identified by molecular method, and the effects of different concentrations (45%, 75%, and 90%), medium pH (6, 7, and 9), temperatures (30 and 37 °C), and incubation times (24, 48, and 72 h) of the filtrates on their anti-biofilm formation properties were investigated. Anti-biofilm assay was performed using the diffusion test and microtiter assay. The parameters examined included the diameter of the inhibition zone of each well and the optical density of the filtrate solution. Molecular identification based on ITS rDNA regions showed that the fungal isolates in this study were Schizophyllum commune (strain JSB2), Coniothyrium sp. (strain JB1-3), and Fusarium sp. (strain JBB2). Antibacterial assay showed that, among the culture filtrates obtained from all fungi, that from Fusarium sp. strain JBB2 exhibits the highest inhibitory activity. Biofilm inhibition assay further revealed optimum fungal culture filtrate activities at pH 7.